Clinical results and 30-day outcomes of self-expanding transcatheter aortic valves: comparative case-matched analysis of CoreValve® versus ACURATE neo™. (January 2023) - Ivanov, Borko; Eghbalzadeh, Kaveh; Djordjevic, Ilija; Zeriouh, Mohamed; Gerfer, Stephen; Gaisendrees, Christopher; Sabashnikov, Anton; Rustenbach, Christian; Rahmanian, Parwis; Kuhn-Regnier, Ferdinand; Mader, Navid; Adam, Matti; et al.
Background: Transcatheter aortic valve replacement (TAVR) is associated with excellent results in patients with severe aortic stenosis. In highly calcified aortic anuli with increased risk of annulus rupture and in favor of the supra-annular design, self-expandable prostheses are frequently used. In this regard, we aimed to perform a comparative analysis of clinical and 30-day outcomes after TAVR using the self-expanding CoreValve ® Evolut R or ACURATE neo™ prosthesis. Methods: Out of 343 consecutive patients treated with either CoreValve ® Evolut R or ACURATE neo™ from January 2014 to December 2017, 76 patients were assigned each per group after 1:1 propensity score matching in regard of preoperative characteristics. Pre- and periprocedural outcomes were retrospectively collected and assessed. Outcomes at 30 days are reported according to the established Valve Academic Research Consortium (VARC-2) criteria. Results: Device success and 30-day survival accounted for 93.4% ( n = 71), respectively 97.4% ( n = 74) in both groups (p = 1.00). No statistically significant differences regarding clinical parameters were observed. The combined safety endpoint at 30 days was comparable (84.2% ( n = 64) CoreValve ® vs 85.5% ( n = 65) ACURATE neo™; p = 0.848). Except a trend toward higher stroke (p = 0.08) and pacemaker (p = 0.07) rate in the CoreValve ® group, major vascular complications, incidence of life-threatening or disabling bleeding, and incidence of postoperative acute kidney injury were comparable. Postoperative hemodynamic parameters showed no significant differences between the implanted valves. Conclusion: Both self-expandable prostheses showed good postoperative hemodynamic performance with a low incidence of severe paravalvular leakage, all- cause mortality, and comparable clinical outcomes.